Etika Komunikasi Islam ETIKA KOMUNIKASI ISLAM ANTARA GURU DAN MURID DALAM KITAB TAZKIRAH AS-SAMI‘ WA AL-MUTAKALLIM FI ADAB AL-‘ALIM WA AL-MUTA‘ALLIM - Irham Dongoran; Daryanto Setiawan; Ahmad Rifandy (Program Studi Komunikasi dan Penyiaran Islam, 2022)
This study aims to determine the form of Islamic communication ethics of students to teachers used by Ibn Jama'ah and as a solution to solving problems of communication between students and teachers. This type of research is library research with a descriptive qualitative approach, the primary data source is the book Tazkirah As-Sami‘ Wa Al-Mutakallim Fi Adab Al-‘Alim Wa Al-Muta‘Allim”